The Impact of Non-Tariff Measures on the Exporting of Agricultural Products of Cambodia - Lim, Siphat (International Journal of Economics and Financial Issues, 2024)
The production and exporting of agricultural products were considered one of the most important roles of the Cambodian people. In the free trade world, tariff measures were not determined to be the main obstacle to moving products from one country to worldwide, but non-tariff measures, NTMs, were defined to be the main problem nowadays. An empirical investigation using the gravity model with four classes of NTMs: SPS, TBT, PSI, and NTB was carried out to assess the impact of Cambodia’s exported agricultural products abroad. In order to generate robust standard errors for hypothesis testing, the Ordinary Least Square (OLS) estimation method was combined with the bootstrapping technique. The results of this research supported the gravity model hypothesis, however, SPS and PSI were negatively affecting Cambodia’s exporting at significant levels of 10 percent and 1 percent, respectively, while the TBT measure had a positive influence on trade at a level of significant of 1 percent. In contrast, the NTB class had no significant impact on exports.